2019
DOI: 10.3389/fmats.2019.00098
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Conducting, Biodegradable and Biocompatible Copolymers for Biomedical Applications

Abstract: Electroactive biomaterials are a new generation of "smart" biomaterials based on intrinsically conducting polymers (ICP). Among them, poly(3,4-ethylenedioxythiophene) (PEDOT), polypyrrole (PPy) and polyaniline (PANI) are well known conducting polymers that present excellent electrical and optical properties emerging as main candidates for potential biomedical applications. Additionally, the biodegradability of biomaterials is very useful and desirable. In this context, biodegradable polymers based on polyester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 105 publications
0
32
0
Order By: Relevance
“…These newly tailored materials were named as biodegradable conducting polymeric materials having mixed advantageous properties of both conducting polymers and biodegradable polymers (da Silva & Córdoba de Torresi, 2019). combined by ester linkages, appeared as a promising candidate due to tailored properties of both the polymers and attracted the attention of researchers as sustainable alternatives for application in medical fields (Figure 3).…”
Section: Conduc Ting P Olymer Smentioning
confidence: 99%
See 1 more Smart Citation
“…These newly tailored materials were named as biodegradable conducting polymeric materials having mixed advantageous properties of both conducting polymers and biodegradable polymers (da Silva & Córdoba de Torresi, 2019). combined by ester linkages, appeared as a promising candidate due to tailored properties of both the polymers and attracted the attention of researchers as sustainable alternatives for application in medical fields (Figure 3).…”
Section: Conduc Ting P Olymer Smentioning
confidence: 99%
“…to overcome the problem of biodegradability and electroactive performances are (i) block copolymers in which modified electroactive oligomers of conducting polymers were connected with degradable ester linkages and (ii) copolymerization of altered biodegradable and electroactive macromonomers based on polyesters prepared in the first step, with conducting polymers (da Silva & Córdoba de Torresi, 2019).…”
Section: Ne W B Iodeg R Adab Le Conduc Ting P Olymer Smentioning
confidence: 99%
“…In order to develop electroactive biomaterials for biomedical applications, grafting of biocompatible and biodegradable polymers such as poly(caprolactone) (PCL), poly(d,l-lactic acid) (PDLA, PLLA), poly(glycolic acid) (PGA) with conducting polymers has gained much attention as a novel approach. To summarize the developing research on the synthesis of conducting polymer-based biomaterials and improvement of their properties after grafting, very recently, Sliva et al [68] presented a good review article. Mainly, there are two ways to generate such conducting graft polymers: (i) attachment of electroactive oligomers to the biodegradable polymers via ester linkage ( Figure 7A) and (ii) subsequent synthesis of electroactive, biodegradable polyesters macromonomer followed by polymerization of conductive monomers ( Figure 7B).…”
Section: Covalent Grafting Of Conducting Polymersmentioning
confidence: 99%
“…Schematic illustrations for synthesis of (A) electroactive oligomers and block copolymers and (B) electroactive macromonomers and graft copolymers. Reproduced with permission[68].…”
mentioning
confidence: 99%
“…The idea to mix biocompatible material and conductive polymers to create new composite biocompatible conductive materials is not novel. Conductive polymers allow excellent control of the electrical stimulus, possess very good electrical and optical properties, have a high conductivity/weight ratio, and can be made biocompatible and biodegradable [ 2 , 31 , 32 ]. Moreover, it has been shown that many natural-based polymers like albumin or cellulose and even some synthetic polymers are perfect biodegradable biomaterials [ 33 ].…”
Section: Introductionmentioning
confidence: 99%